Escolha e desempenho no trabalho de adultos com deficiência mental - Escobal, Giovana (Universidade Federal de São Carlos, 2007)
Choice making is a fundamental skill for all individuals. Choice opportunities are related with important questions of human development, and of paramount importance to the development of clinical and educational programs for mentally retarded individuals. Despite its practical importance, little is known about the effects that choice may have in the work environment of this population. In this study, choice was investigated under two conditions: with and without environmental work support. Work performance was assessed as a function of conditions chosen. First, four mentally retarded adults learned to perform a work task under those two conditions. The task consisted of assembling notebook covers. An MDF (medium density fiber) board measuring 30cm by 40 cm, was employed as work support and displayed several low relief recipients to suit its different components and was designed to provide immediate feedback, to increase or maintain the rate of work response and to prevent errors during the task routine. A number of small pieces of paper, 2cm by 2cm, in different colors, pieces of thin cardboard, 10cm by 8cm, glue sticks, candies and chocolate bars previously chosen by the participants in preference tests were used. The study took place in quiet, well lit and ventilated room at the participants institution, isolated from other workshop clients. Following initial training the participants worked individually either under multiple schedules or under concurrent-chain schedules according to a multiple-element design. When the multiple schedules condition was on, the components were either presence or absence of work support, quasi-randomly distributed. Under the concurrent-chain schedules conditions a FR-1 was used on the first link, and either one of the two work alternatives, on the second link. Throughout the study, whenever the participant presented an error, verbal, gestual prompts and model were provided. Initially verbal prompts were provided and, if necessary, by gestual, verbal plus gestual prompts, and model, in this sequence, until the target responses were emitted. In relation to the parameters analyzed, the number of errors and prompts were higher working without work support than working with it, during the teaching phase. Baseline on task performance, under multiple schedules, showed prompts lower in the work support component in relation to the no work support component. Under concurrent chain schedule, however, the percentage of prompts under work support was higher in relation to the no work support alternative. As far as time spent to complete the task, in the teaching phase, two participants finished the work activity faster in the component without support. During baseline on task performance, under multiple schedules and chain concurrent schedules, three participants finished the task faster working with the work support. The results showed a preference for the work support alternative for two participants, while the other two distributed their choices evenly between the two alternatives. With the work support, time on task was relatively lower as compared to the no work support. The number of errors by P3 was different from the other participants, who showed a much smaller number of errors evenly distributed between the experimental conditions. Working with support was preferable from the participant s point of view. Besides that, under supported work, participants finished the task faster and the number of errors was kept in a low level. The participants could choose independently of his performance in the parameters analyzed. The study brings a contribution to vocational training programs for the severely retarded and to the development of a common interface with the areas of Behavior Analysis, Special Education and Ergonomics and brings practical implications for the design of teach procedures for mentally retarded.
Keywords: Educação especial; Escolha (Psicologia); Trabalho; Adultos com deficiência mental; Esquemas concorrentes; Arranjo instrucional; Choice; Work; Mentally retarded adults; Instructional material; Concurrent schedules; Self-determination; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL